Regularity of self-reported daily dosage of mood stabilizers and antipsychotics in patients with bipolar disorder - Maximilian Pilhatsch; Tasha Glenn; Natalie Rasgon; Martin Alda; Kemal Sagduyu; Paul Grof; Rodrigo Munoz; Wendy Marsh; Scott Monteith; Emanuel Severus; Rita Bauer; Philipp Ritter; et al. (International Journal of Bipolar Disorders, 2018)
Abstract Background Polypharmacy is often prescribed for bipolar disorder, yet medication non-adherence remains a serious problem. This study investigated the regularity in the daily dosage taken of mood stabilizers and second generation antipsychotics. Methods Daily self-reported data on medications taken and mood were available from 241 patients with a diagnosis of bipolar disorder who received treatment as usual. Patients who took the same mood stabilizer or second generation antipsychotic for ≥ 100 days were included. Approximate entropy was used to determine serial regularity in daily dosage taken. Generalized estimating equations were used to estimate if demographic or clinical variables were associated with regularity. Results There were 422 analysis periods available from the 241 patients. Patients took drugs on 84.4% of days. Considerable irregularity was found, mostly due to single-day omissions and dosage changes. Drug holidays (missing 3 or more consecutive days) were found in 35.8% of the analysis periods. Irregularity was associated with an increasing total number of psychotropic drugs taken (p = 0.009), the pill burden (p = 0.026), and the percent of days depressed (p = 0.049). Conclusion Despite low missing percent of days, daily drug dosage may be irregular primarily due to single day omissions and dosage changes. Drug holidays are common. Physicians should expect to see partial adherence in clinical practice, especially with complex drug regimens. Daily dosage irregularity may impact the continuity of drug action, contribute to individual variation in treatment response, and needs further study.